Correlation and Linear Regression Tests: Projected Deforestation Due to New Capital Development in East Kalimantan - Isman, I; Widodo, Prima Aryo; Setyowati, Yuli (Universitas Muhammadiyah Surakarta, 2023)
Linear regression analysis was used in this research to investigate the correlation between deforestation and the number of climate villages. The results showed a significant association between climate villages and deforestation rates, as the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. This suggests that climate village initiatives or policies have a tangible impact on deforestation patterns. The study's findings can contribute to natural resource management and environmental conservation strategies. This finding highlights the pivotal role of climate villages in reducing deforestation rates. Therefore, environmental and development policies can be tailored to actively support these initiatives. The study provides both conceptual insights into variable relationships and practical guidance for environmental conservation and sustainable development efforts.